We have been given an expression
. We have been given steps how Chris tried to solve the given expression. We are asked to choose the correct option about Chris's work.
Let us simplify our given expression.
Using exponent property,
, we cab rewrite our given expression as:
![\left( 4^{-2+(-3)} \right)^{3}](https://tex.z-dn.net/?f=%5Cleft%28%204%5E%7B-2%2B%28-3%29%7D%20%5Cright%29%5E%7B3%7D)
![\left( 4^{-5} \right)^{3}](https://tex.z-dn.net/?f=%5Cleft%28%204%5E%7B-5%7D%20%5Cright%29%5E%7B3%7D)
Now we will use exponent property
to further simplify our expression.
![\left( 4^{-5} \right)^{3}= 4^{-5\cdot 3}](https://tex.z-dn.net/?f=%5Cleft%28%204%5E%7B-5%7D%20%5Cright%29%5E%7B3%7D%3D%204%5E%7B-5%5Ccdot%203%7D)
![\left( 4^{-5} \right)^{3}= 4^{-15}](https://tex.z-dn.net/?f=%5Cleft%28%204%5E%7B-5%7D%20%5Cright%29%5E%7B3%7D%3D%204%5E%7B-15%7D)
Therefore, Chris made mistake in step 2.
13. You add the 8 and the 5
Translation by h (right) and k (up)
g(x)=f(x-h)+k
=f(x-4)^2+2
so h=4, k=2
horizontal translation (to the right) is h=+4, but is shown as -4 for the translation value.
Answer: you wrote it wrong
Step-by-step explanation:
Answer:
It is not a function
Step-by-step explanation:
The plot shows (1, 1) and (1, 3) are both defined by the relation. It does not pass the "vertical line test", which requires the relation be single-valued everywhere.